Changing the availability and positioning of more vs. less environmentally sustainable products: a randomised controlled trial in an online experimental supermarket - Jostock, C; Luick, M; Jebb, SA; Pechey, R (Elsevier, 2024)
Food purchasing behaviours are shaped by the choices available to shoppers and the way they are offered for sale. This study tested whether prominent positioning of more sustainable food items online and increasing their relative availability might reduce the environmental impact of foods selected in a 2x2 (availability x position) factorial randomised controlled trial where participants (n=1179) selected items in a shopping task in an experimental online supermarket. The availability intervention added lower-impact products to the regular range. The positioning intervention biased product order to give prominence to lower-impact products. The primary outcome was the environmental impact score (ranging from 1 “least impact” to 5 “most impact”, of each item in shopping baskets) analysed using Welch’s ANOVA. Secondary outcomes included interactions (analysed via linear regression) by gender, age group, education, income and meat consumption and we assessed intervention acceptability (using different frames) in a post-experiment questionnaire. Compared to control (mean=21.6), mean eco quintile score was significantly reduced when availability & order was altered (-2.30; 95%CI: -3.04; -1.56) and when order only was changed (-1.67; 95%CI: -2.42; -0.92). No significant difference between availability only (-0.02; 95%CI: -0.73; 0.69) and control was found. There were no significant interactions between interventions or by demographic characteristics. Both interventions were acceptable under certain frames (positioning emphasising lower-impact products: 70.3% support; increasing lower-impact items: 74.3% support). Prominent positioning of more sustainable products may be an effective strategy to encourage more sustainable food purchasing. Increasing availability of more sustainable products alone did not significantly alter the environment impact of products selected.